Demystifying the contractual duty of care of Islamic banks in Malaysia - Abu Bakar, Noor Mahinar; Mohd Yasin, Norhashimah (IIUM Journal Publication Unit, 2019)
The general relationship between a bank and customer is contractual in nature. For conventional banks, the banker-customer relationship is based on the debtor-creditor relationship with the bank earning a profit from a spread made between interest charged on the borrower of funds and interest paid to the depositors. In Islamic banking, due to the different contractual transactions of Islamic banking operation, it is based on a multi-contractual relationships. However, bank consumers perceive that banks enhance their profits by treating consumers unfairly and failing to take responsibility when things go wrong. This study examines the duty of care of conventional and Islamic banks towards bank consumers. It also focuses on the Islamic banks’ duty of care from the perspective of maqāṣid al-Sharī‛ah, to those who use their services. Adopting the doctrinal analysis method, this study analyses and compares the duty of care of both conventional and Islamic banks. Findings of this study include that misconduct by banking industries remains rife and that unfair treatment of customers are frequent. As for Islamic banks, the maqāṣid al-Sharī‛ah based duty of care is found missing in their Islamic banking operation. This study suggests that the duty of care for both banks should be reformed to improve bank consumers’ experience. For Islamic banks, an improved standard is useful in performing their duties based on Islamic values.